Assistência de enfermagem ao paciente portador de tuberculose em unidade básica de saúde : elaboração de instrumento - Oliveira, Rafaelle Lopes de (2014)
Tuberculosis continues to receive special attention from health professionals and society as a whole. The role of nurses is particularly important in the implementation of actions to control the disease. It is known that the customer treatment suffers stigma and is subject to various physical and psychological changes. Therefore, the possibility of a more organized and targeted monitoring could minimize such consequences, ensuring greater compliance. In this context it is the need to collaborate to implement the Care System Nursing. The study aimed to: identify the nursing diagnoses in patients with tuberculosis; create an instrument for systematization of nursing care. This was a descriptive, exploratory study. Was performed on a Unit Primary Health Care, linked to Government of Fortaleza - Ceará. The population consisted of 13 patients undergoing treatment. Data collection was conducted in February 2014. Information collected for phase identification of nursing diagnoses had as its starting point an instrument prepared by the Ministry of Health as a basis for the construction of diagnoses, outcomes and interventions was used to NANDA Taxonomy II and the links between NANDA, NIC and NOC. 11 nursing diagnoses were identified, the most common being: Ineffective breathing pattern; nausea; activity intolerance; imbalanced nutrition: less than body requirements; poor knowledge about preventive measures, control, treatment and self-care; hyperthermia; fatigue; Impaired skin integrity; noncompliance; social isolation. From these, the expected outcomes and nursing interventions were established to make the care plan. We conclude that it is possible to develop an instrument for systematization of nursing care to patients with tuberculosis, in order to improve quality and ensure continuity of nursing care.